Pravni vidiki postavitve in obratovanja vetrnih elektrarn - Tratnik, Matjaž (Podjetje in delo, 2023)
In this paper, the author discusses the property-law aspects of the installation and operation of wind farms (wind turbines). Two key questions arise here. The first is the question of the legal relationship between the wind turbine and the immovable property on which it is built. The second, which is linked to the first, is the question of security rights in rem upon wind turbines. The author posits that wind turbines are, in most cases, appurtenances to the immovable properties. However, if they are part of a wind farm or if they supply electricity to off-grid facilities, they may qualify as component parts. As regards the security rights, a distinction should be made between wind turbines installed on own immovable properties and wind turbines installed on third-party immovable properties. In the former case, the wind turbines are subject to a mortgage on the immovable property, regardless if they are component parts or appurtenances. However, if the wind turbines are located on third-party immovable property and are component parts, it is possible for the investor to acquire a building right, which can be independently mortgaged. If the wind turbines are not component parts, but appurtenances, they cannot be subject to a potential mortgage on the immovable property, but are treated as movable property in their own right and, as such, can be subject to non-possessory movable security rights.
Keywords: lastninska pravica; nepremičnine; Okoljsko pravo (evropsko pravo); premičnine; stavbna pravica; stvarno pravo; vetrne elektrarne